CASE REPORT: Serial Cases of False-Positive Flow-Cytometry T Cell Crossmatch Associated With Anti–Blood Type Antibodies in Patients Undergoing ABO-Incompatible Kidney Transplantation - Hayashi, Ayaka; Yamamoto, Izumi; Kawabe, Mayuko; Kobayashi, Akimitsu; Ito, Makoto; Hotta, Kiyohiko; Shinohara, Nobuo; Tasaki, Tetsunori; Yokoo, Takashi; Iwami, Daiki (Frontiers in Immunology, 2022)
Background: A positive flow-cytometry T cell crossmatch (FTXM) has important prognostic implications, even when the complement-dependent cytotoxicity crossmatch is negative. Recent studies have shown that ABO incompatibility is associated with positive FTXM, but the underlying mechanism remains poorly understood. Cases: In five ABO blood type O recipients of kidneys from wives with type B, FTXM was positive but complement-dependent cytotoxicity crossmatch was negative. Application of a solid-phase technique (LABScreen) revealed no case with antibodies to donor-specific human leukocyte antigen. After removal of type B antibodies from patient sera, FTXM was negative for all five patients. In one tested case, the eluate prepared from the donor’s T lymphocyte agglutinated only type B red blood cells, implying the existence of blood type B substances on donor T lymphocytes. Discussion: False-positive FTXM reflects blood type B substrates bound to T lymphocytes. Repeat FTXM after incubation with donor-type red blood cells (to adsorb anti-ABO antibodies) was negative. This phenomenon explains the discrepancy between FTXM and solid-phase bead assays. Demonstration of type B substances on donor T lymphocytes is necessary before absolute test validity is confirmed. Conclusion: False-positive FTXM may be associated with type B antibodies bound to T lymphocytes when a blood type O recipient receives tissue from a type B donor. This phenomenon explains the false-positive FTXM observed in the setting of ABO-incompatible kidney transplantation.